2012
DOI: 10.1111/j.1365-2672.2012.05281.x
|View full text |Cite
|
Sign up to set email alerts
|

Cronobacter species (formerly known as Enterobacter sakazakii) in powdered infant formula: a review of our current understanding of the biology of this bacterium

Abstract: Summary Cronobacter species (formerly known as Enterobacter sakazakii) are opportunistic pathogens that can cause necrotizing enterocolitis, bacteraemia and meningitis, predominantly in neonates. Infection in these vulnerable infants has been linked to the consumption of contaminated powdered infant formula (PIF). Considerable research has been undertaken on this organism in the past number of years which has enhanced our understanding of this neonatal pathogen leading to improvements in its control within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 105 publications
1
97
0
1
Order By: Relevance
“…However, this source now seems to be unlikely, as none of the vaginally delivered infants developed signs of infection until several days after birth and it is also unlikely that Cronobacter constitute a part of the vaginal microflora (Yan et al, 2012;Hunter & Bean, 2013). In addition, Biering et al (1989) observed that infants who showed Cronobacter meningitis had all received reconstituted powdered-milk formula before falling ill.…”
Section: Infantile or Neonatal Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this source now seems to be unlikely, as none of the vaginally delivered infants developed signs of infection until several days after birth and it is also unlikely that Cronobacter constitute a part of the vaginal microflora (Yan et al, 2012;Hunter & Bean, 2013). In addition, Biering et al (1989) observed that infants who showed Cronobacter meningitis had all received reconstituted powdered-milk formula before falling ill.…”
Section: Infantile or Neonatal Infectionsmentioning
confidence: 99%
“…Up to 50 % of adults with Cronobacter infection had an underlying malignancy (Lai, 2001;See et al, 2007). Interestingly, Cronobacter have been linked to or should be considered as a pathogen that may cause sepsis, conjunctivitis, aspiration pneumonia in stroke patients, osteomyelitis, diarrhoea, acute cholecystitis, wound infections, abscesses associated with indwelling catheters and urinary tract infections (Gosney et al, 2006;Friedemann, 2009;Flores et al, 2011;Yan et al, 2012;Tsai et al, 2013).…”
Section: Infections Associated With Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this issue, Singh et al 3 investigated the interaction between biofilm formation, extracellular polysaccharide substance (EPS) production and AHL production during biofilm formation in Cronobacter sakazakii, a re-emerged foodborne pathogen that causes a variety of infections in all age groups; however, neonates and elderly individuals are at a higher risk and remain the most susceptible age groups for life-threatening, invasive disease. 4 While infantile Cronobacter infections are often linked to the consumption of reconstituted, temperature-abused, intrinsically or extrinsically contaminated powdered formulas, these organisms are also found associated with other foods and food production environments, such as that of manufacturing facilities of dried foods, thereby posing a risk to susceptible consumers. 5 Previous studies by Lehner et al and da Silva Araujo et al reported the presence of 2 and 3 QS molecules in different Cronobacter spp., respectively.…”
mentioning
confidence: 99%
“…Whereas Cronobacter strains are ubiquitous and have been isolated from various foods and environments (Turcovsky et al 2011;Holy and Forsythe 2014) the main vehicle for their transmission in neonatal infections is rehydrated powdered infant formula (PIF) (Yan et al 2012;Holy and Forsythe 2014). In comparison with other Enterobacteriaceae, members of the genus Cronobacter are considerably resistant to desiccation Osaili and Forsythe 2009;Walsh et al 2011;Jaradat et al 2014) and this property contributes to their survival in PIF.…”
Section: Introductionmentioning
confidence: 99%